The effects of transformational leadership and ERP system self-efficacy on ERP system usage. Issue 6 (23rd August 2014) - Elkhani, Naeimeh; Soltani, Sheida; Ahmad, Mohammad Nazir
Abstract : Purpose: During the past decade, there has been vast investment in Enterprise Resource Planning (ERP) system packages, in addition to a significant increase in the importance of acceptance by users of the ERP system regarding the success or failure of ERP implementation. Accordingly, researchers have attempted to identify the external factors which influence ERP system acceptance. Our work is motivated by the realization that transformational leadership (TL) and ERP system self-efficacy are critical external factors that can affect ERP system acceptance. Design/methodology/approach: A framework has been developed from a study of literature in the field of transformational leadership, ERP system self-efficacy and the technology acceptance model (TAM). A survey utilizing a questionnaire was used to collect data and a total of 151 usable responses were analysed by using the partial least squares (PLS) method. Findings: The results of the study indicate that TL can either directly or indirectly influence perceived usefulness (PU) via the assimilation of self-efficacy in a positive manner. Also, TL has been found to have a positive influence on perceived ease of use (PEU) both directly and indirectly via application of self-efficacy measures. Research limitations/implications: The findings were drawn from two Iranian companies, hence the results are not necessarily generalizable to other nations and other cultures. Practical implications: Management should provide transformational leadership development programs for their ERP leaders and encourage them to implement transformation in a manner that could increase assimilation and application of self-efficacy when using the ERP system. Originality/value: Our study can provide ERP managers with a better understanding of how they can use transformational leadership behavior and skills in motivating and enhancing employees' self-efficacy in order to achieve ERP system usage success.